Cation-selective two-dimensional polyimine membranes for high-performance osmotic energy conversion - Zhen Zhang; Preeti Bhauriyal; Hafeesudeen Sahabudeen; Zhiyong Wang; Xiaohui Liu; Mike Hambsch; Stefan C. B. Mannsfeld; Renhao Dong; Thomas Heine; Xinliang Feng (Nature Communications, 2022)
Two-dimensional (2D) membranes are emerging candidates for osmotic energy conversion but the trade-off between ion selectivity and conductivity remains the key bottleneck. Here, the authors demonstrate a fully crystalline imine-based 2D polymer membrane capable of combining excellent ionic conductivity and high selectivity for osmotic energy conversion.